2020
DOI: 10.3389/fonc.2020.00807
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acidosis in the Presence of Glucose Diminishes Warburg Effect in Lung Adenocarcinoma Cells

Abstract: Lactic acidosis (3 to 40 mM, pH < 6.9) is a condition found in solid tumors because tumor cells have a high rate of glucose consumption and lactate production even in the presence of oxygen; nevertheless, the microenvironment might still provide a sufficient glucose supply. Lactic acidosis has been proposed to shift metabolism from aerobic glycolysis toward oxidative phosphorylation (OXPHOS). We tested if lung tumor cells cultured under lactic acidosis shift their metabolism from glycolysis to OXPHOS by consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Our study found that PKM2 expression was increased in the spinal cord after CFA injection and was accompanied by altered pain behavior. Simultaneously, we detected an increase in GLUT1 and glycolysis product lactic acid levels, which may be due to increased glucose uptake and increased glycolysis activity (52). These results show that PKM2 may be involved in the development of CFA inflammatory pain.…”
Section: Discussionsupporting
confidence: 56%
“…Our study found that PKM2 expression was increased in the spinal cord after CFA injection and was accompanied by altered pain behavior. Simultaneously, we detected an increase in GLUT1 and glycolysis product lactic acid levels, which may be due to increased glucose uptake and increased glycolysis activity (52). These results show that PKM2 may be involved in the development of CFA inflammatory pain.…”
Section: Discussionsupporting
confidence: 56%
“…4 d. LDHA expression was consistent with the lactic acid measurement; its expression was lower in MCF-7 cells than in normal MCF-10A cells, although there was no significant difference between the two groups. LDHA expression is regulated by hypoxia-inducible factor alpha (HIF-1α) 16 , 17 . The expression of HIF-1α was very low in MCF-10A cells, and the level of expression increased as the degree of malignancy of the breast cancer cells increased.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, altered glucose metabolism—the Warburg effect [ 90 ]—promoted the progression of HNSCC, which is partially attributed to the solute carrier family 2 member A4 (SLC2A4, or glucose transporter 4, GLUT4) and tripartite motif-containing 24 (TRIM24) pathway [ 91 , 92 ]. Lactic acidosis-induced GLUT4 overexpression was also found in lung cancer cells [ 93 ]. Currently, pembrolizumab and nivolumab’s success has been based on a common biomarker (e.g., PD-1) in several types of cancer.…”
Section: Discussionmentioning
confidence: 99%